Administration Diagnosis of quality of work life dimensions: A survey of a sample of employees of the Northern Gas Filling Company in Nynawa - حميد سجى نذير (Journal of Economics and Administrative Sciences, 2025)
The primary objective of the present research is to diagnose the most mportant imensions of quality of work life in a sample of individuals working in the Northern Gas Filling Company in Nynawa. The study sample consisted of 140 employees of the Northern Region Filling Company in even ,Through a questionnaire prepared for this purpose. The study concluded that there are five main factors that are considered to be measure of the quality of working life and are based on their importance: Empowerment, organizational health, internal work environment, motivation, development and training of workers. The study recommended that the organization should payattention to these factors when working to adopt the quality of work life and work to provide it correctly. The basic contribution of the present study is to provide a classification of quality of life factors based on the opinions of the employees of the research society. This gives practical importance to the study as the organizations can benefit from its results in providing these factors and work to strengthen them because of their high impact on the quality of work life and as a A measure of the quality of working life.